Islamic Banks after the 2008 Crisis: Symptoms of the Second Round Crisis and Performance of Sharia Commercial Banks during the Period 2012-2017 - Enayatullah, Imam Haroki; Amalia, Euis; Rini, Rini (Moneter: Jurnal Keuangan dan Perbankan, 2023)
The Islamic banking system has long been believed to possess resilience in the face of crises, some even asserting its resistance to such challenges. To validate the aforementioned notion, an analysis of the efficiency performance of Sharia banking is conducted after the occurrence of what is referred to as the Second Round Crisis. This is undertaken due to the discovery that the impact of a crisis might not necessarily be felt during its onset, but rather after its passing. The research case study is Sharia Commercial Banks in Indonesia during the period 2012-2017. The research employs a parametric approach, namely the Stochastic Frontier Analysis Panel (SFA)  Greene's approach (2005) to examine the data. The research found that all examined samples experienced a decrease in efficiency in the year 2014. The data also reveal an increase in Non-Performing Financing (NPF) and a decrease in Return on Assets (ROA) during the same period. These findings reveal the presence of a second-round crisis phenomenon affecting the Sharia Commercial Banks in this year. Following this period, there was a gradual improvement in both efficiency and other ratios. In conclusion, it can be inferred that Sharia banks, particularly in Indonesia, are not resistant to crises.